Biochemical and in silico study of leaf extract from Rumex dentatus against Staphylococcus aureus - Md. Moniruzzaman; Mst. Merina Mostari; Shirmin Islam; Mst. Maskera Jinnah; Jui Biswas; Suvro Biswas; Shahriar Zaman; Md. Abu Saleh; Md. Salah Uddin (Journal of Advanced Biotechnology and Experimental Therapeutics, 2023)
Rumex dentatus is a medicinal plant with a variety of bioactive components that can be used to treat infections and multidrug-resistant (MDR) microbes. MDR microbes associated with infection pose a real threat and the available antibiotics can no longer be used to control or kill those bacteria. Thus, the study aimed to ascertain the antibacterial activity of Rumex dentatus leaf extract and identify a potent compound that can be used as a drug developmental agent may against Staphylococcus aureus. Disc diffusion method, mortality assay of brine shrimp, and DPPH free radical scavenging assay were carried out for in vitro analysis. Standard computational tools and servers such as Pymol, PyRx, and Discovery Studio were used for carrying out the in silico studies. Staphylococcus aureus was isolated from the infected area of eczema sufferers and identified through morphological, biochemical, and 16SrRNA sequence analysis. Rumex dentatus leaf extract was diluted with methanol and it showed the maximum zone of inhibition (14.33 ± 0.68 mm) after applying it against Staphylococcus aureus at the dose of 150µg/disc. Furthermore, the extract revealed remarkable antioxidant activity and the death rate of brine shrimp and leaf extract concentration were positively connected. Finding pharmacological targets with a high affinity for the FosB (4nb2) protein, which controls antibiotic resistance in Staphylococcus aureus, was done via molecular docking. 1-Alpha-18O-1,25-dihydroxycholecalciferol (CID- 5280453), Androstan-3-ol, 9-methyl-(3 beta,5 alpha) (CID- 22215820), Phenylacetaldehyde (CID- 998), and Benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy- methyl ester (CID- 62603) substances had binding energies of -6.8 Kcal/mol, -6.6 Kcal/mol, -5.6 kcal/mol, and -5.5 kcal/mol, respectively. As an organic source of medicines, Rumex dentatus leaf extract could thus be used to combat the antimicrobial-resistant pathogen. [ J Adv Biotechnol Exp Ther 2023; 6(1.000): 286-300]